Construction of Indigenous Community Gardens by the Company as Land Conflict Resolution - Rahmad Hendra; Firdaus Firdaus; Samariadi Samariadi (Universitas Kuningan, 2022)
The study was conducted in the villages, Bencah Kelubi and Subarak. Both villages have oil palm plantation companies. The study aims to scrutinize the influence of oil palm plantations, particularly the development and efforts in resolving land disputesâ”€ the indigenous people and the so-called company in Kampar Regency. This study employed descriptive analysis involving qualitative patterns. The study revealed some points. In Subarak village, the investor of an oil palm plantation built a garden for indigenous people. In addition, prior to the investment, they apply the principle of Free, Prior, and Informed Consent (known as PADIATAPA). On the other hand, the investors (oil palm plantation companies) did not fulfill the commitment to build gardens for the community. Also, they disregarded the principle of PADIATAPA. In conclusion, employing the PADIATAPA principle at the initial stage could significantly lessen the conflicts between oil palm plantation companies and indigenous people.